2008
DOI: 10.2118/104380-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Permeability Model for Coal and Other Fractured, Sorptive-Elastic Media

Abstract: This paper describes the derivation of a new equation that can be used to model the permeability behavior of a fractured, sorptive-elastic media, such as coal, under variable stress conditions commonly used during measurement of permeability data in the laboratory. The model is derived for cubic geometry under biaxial or hydrostatic confining pressures. The model is also designed to handle changes in permeability caused by adsorption and desorption of gases from the matrix blocks. The model equations can be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(72 citation statements)
references
References 14 publications
0
72
0
Order By: Relevance
“…Other stressbased coal permeability models include Harpalani and Chen (1997), Gilman and Beckie (2000), Shi and Durucan (S-D) (2004), and Cui and Bustin (C-B) (2005). Based on cubic geometry, Robertson and Christiansen (2006) described the derivation of a new equation that can be used to model the permeability behavior of a fractured, sorptive-elastic medium, such as coal, under variable stress conditions. Ma et al (2011) proposed a permeability model based on the volumetric balance between the bulk coal, solid grains and pores, using the constant volume theory proposed by Massarotto et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Other stressbased coal permeability models include Harpalani and Chen (1997), Gilman and Beckie (2000), Shi and Durucan (S-D) (2004), and Cui and Bustin (C-B) (2005). Based on cubic geometry, Robertson and Christiansen (2006) described the derivation of a new equation that can be used to model the permeability behavior of a fractured, sorptive-elastic medium, such as coal, under variable stress conditions. Ma et al (2011) proposed a permeability model based on the volumetric balance between the bulk coal, solid grains and pores, using the constant volume theory proposed by Massarotto et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…They simplified the cleat system with cubic matrix blocks and considered the following three factors as contributors to changes in cleat width and matrix block size when different stresses were applied to coal: (1) pore volume compressibility; (2) matrix compressibility governed by mechanical elastic moduli; and (3) sorption-induced strain (Robertson and Christiansen, 2006).…”
Section: Robertson and Christiansen Model (2006)mentioning
confidence: 99%
“…Poisson's ratio is 0.31, and the Langmuir volume P L ¼ 2.86 MPa, which was obtained by sorption tests. Robertson, (2005Robertson, ( , 2006 obtained Langmuir strains of Anderson and Gilson coals tested by N 2 , which are extremely small, and the average value is as low as 0.0025. They also obtained the average compressibility change rate a ¼ 0.44 MPa À1 combining the study of McKee et al (1988).…”
Section: Basic Parameters For Coalmentioning
confidence: 99%
“…A sensitivity study showed that permeability, cleat spacing and in situ stresses had a significant influence on CBM production, whereas Young's modulus, Poisson's ratio and Langmuir pressure were found to have a small impact. Robertson and Christiansen (2008) proposed a permeability model for coal and other fractured sorptive-elastic media. The cubic geometry model was used as the basis instead of the matchstick model.…”
Section: Other Modelsmentioning
confidence: 99%